Satellite Monitoring of Anomalous Wildfires in Australia - Bondur, Valery G.; Gordo, Kristina A.; Voronova, Olga S.; Zima, Alla L. (Frontiers in Earth Science, 2021)
Here we present the results of satellite monitoring of wildfires in Australia in 2001-2019. Annual and monthly dynamics of wildfire areas and wildfire-driven CO and СО2 carbon bearing trace gas emissions have been analyzed for the whole territory of Australia and its regions based on satellite data. Abnormally high values of burned-out areas were detected in 2019 in New South Wales, which exceeded the values of previous years 3.5 – 25.8-fold. Also, annual mean volumes of carbon-bearing gas emissions in these regions exceeded the values of previous years 4 – 59-fold for СО and 4.6 – 50-fold for СО2. The increase in the number of wildfires, as well as the CO and СО2 concentrations in the region were due to the abnormally high surface temperatures. According to the monthly mean data of the AIRS instrument (Aqua satellite), it was found that in December 2019, concentrations of carbon monoxide CO (by 9×1017 molec/cm2) exceeded the average values for this month for the period from 2003 to 2018. At the same time, the share of carbon dioxide, СО2 in the atmosphere estimated using the TANSO-FTS (GOSAT) data in December exceeded similar data for 2009-2018 by 15 ppm. The largest areas of wildfires in Australia were detected in the spring and summer months (for the southern hemisphere) from September to December.